Revolutionary Bodies : Chinese Dance and the Socialist Legacy - Wilcox, Emily, 1981- (Book collections on Project MUSE., 2019)
"Revolutionary Bodies is the first primary source-based history of concert dance in the People's Republic of China. Combining over a decade of ethnographic and archival research, it analyzes major dance works by Chinese choreographers staged over an eighty-year period from 1935 to 2015. Using previously unexamined film footage, photographic documentation, performance programs, and other historical and contemporary sources, Emily Wilcox challenges the commonly accepted view that Soviet-inspired revolutionary ballets are the primary legacy of the socialist era in China's dance field. The digital edition of this title includes nineteen embedded videos of selected dance works discussed by the author"--Provided by publisher.